The Model of Learning Profile "Diamond of Personality" to Develop the Learners Agency - Mikhail E. Kushnir; Pavel D. Rabinovich; Kirill E. Zavedensky (National Research Mordova State University, 2022)
Introduction. The implementation of the strategic priorities for the development of education in Russia, as well as the changing demands of interested participants in the educational process actualize questions about the performance of educational organizations, how to measure them, as well as modern education management practices. The use of only normative and criteria-based assessment does not allow achieving the key demanded educational result - the active behavior of the student, because requires different approaches to the organization of educational activities, the construction of collective-individual educational routes, the creation of opportunities for self-determination and self-realization for both students and teachers. The purpose of the article is to describe a model that reflects educational results as a personal potential for a number of parameters of different directions. Materials and Methods. Local and global practices (assessment, evaluation, target and value of learning) have been analyzed. Revealed trends and failures were used as base for new assessment model. Results. The authors researching a lot of evaluation models formulated a simple criterion for the applicability of assessment tools in the form of "the complexity of the tool should not exceed the interest in its results". The proposed model claims to have a reasonable balance of complexity and informativeness: on the one hand, the structure of the parameters is multilevel, on the other hand, it is visualized like octahedron - a diamond crystal. The choice at each level is simple as dichotomy which allows it to be considered an indicator. It should be used as basis of digital learning profile. Discussion and Conclusion. The conclusions made by the authors contribute to the development of tools for assessing the educational result, focused on active educational behavior and using the digital environment for monitoring and accounting. The materials of the article can be useful to teachers and administrators who are interested not only in the traditional sign of compliance with the final tests, but also in the development of educational subjectivity that supports and develops the activity of students.